1994
DOI: 10.1001/archpsyc.1994.03950080019003
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Selegiline in Treatment-Resistant Older Depressive Patients

Abstract: Our results suggest that high-dose selegiline can be an effective antidepressant in treatment-resistant older depressive patients. While the selegiline dose required has nonselective monoamine oxidase effects and thus would not be free of possible tyramine interactions, other advantages suggest that further investigations with selegiline are warranted in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(53 citation statements)
references
References 57 publications
2
50
0
1
Order By: Relevance
“…These findings suggest that the ACTH-treated rats may serve as an animal model for tricyclic antidepressant treatmentresistant depressive conditions. The use of selegiline has been reported to improve the response to various antidepressants in otherwise treatment-resistant patients (6,7). In the present study, the immobility-decreasing effect suggests that selegiline may be effective against tricyclic antidepressant treatment-resistant depression.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These findings suggest that the ACTH-treated rats may serve as an animal model for tricyclic antidepressant treatmentresistant depressive conditions. The use of selegiline has been reported to improve the response to various antidepressants in otherwise treatment-resistant patients (6,7). In the present study, the immobility-decreasing effect suggests that selegiline may be effective against tricyclic antidepressant treatment-resistant depression.…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported that the anti-Parkinson drug selegiline, a selective and irreversible monoamine oxidase (MAO)-B inhibitor, is effective against treatment-resistant depression (6,7). There is increasing evidence that impaired functioning of the mesolymbic dopaminergic system is involved in the pathogenesis of depression, while a common property of antidepressant drugs is their ability to reinforce the dopaminergic system (8).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the best evidence of antidepressant efficacy comes from studies employing larger, nonselective dosages (i.e., 20-50 mg/day) of L-selegiline (e.g., Mann et al 1989;Sunderland et al 1994). This suggests that inhibition of type A enzyme, either alone or in combination with inhibition of MAO Type B, is critical to the MAOIs' antidepressant response .…”
Section: Pharmacologymentioning
confidence: 99%
“…116,117 Subjects in these highdose selegiline trials were maintained on low tyramine or strict MAOI diets. [115][116][117] Case reports and studies have also described the use of MAOIs in combination with other antidepressants, including bupropion with tranylcypromine, RIMAs with SSRIs, and irreversible MAOIs with TCAs. 118-120 The current safety data concerning such combinations are limited and clinicians must exercise appropriate caution.…”
Section: Treatment-refractory Depressionmentioning
confidence: 99%